2017
DOI: 10.7287/peerj.preprints.3278v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pumpkin powdery mildew disease severity influences the fungal diversity of the phyllosphere

Abstract: Pumpkin powdery mildew disease severity influences the fungal diversity of the phyllosphere. PeerJ 6:e4559 https://doi.org/10.7717/peerj.4559Pumpkin powdery mildew disease severity influences the fungal diversity of the phyllosphere Phyllosphere microbiota play a crucial role in plant-environment interactions and are influenced by biotic and abiotic factors. However, there is little research on how pathogen s affect the microbial community. In this study, we collected 16 pumpkin (Cucurbita moschata) leaf sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The analysis of powdery mildew-induced changes in plant leaf microbiota so far rests on field studies with powdery mildew-infected leaf samples (diseased leaves) in comparison to healthy/less infected leaves in Japanese spindle ( Euonymous japonicus ) (Zhang et al ., 2019b), pumpkin ( Cucurbita moschata ) (Zhang et al ., 2018) and English oak ( Quercus robur ) (Jakuschkin et al ., 2016) (reviewed in (Panstruga & Kuhn, 2019)). In the E. japonicus study, the authors noticed a reduction in bacterial and fungal diversity, associated with a general decrease in relative abundance (RA) at the genus level (Zhang et al ., 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of powdery mildew-induced changes in plant leaf microbiota so far rests on field studies with powdery mildew-infected leaf samples (diseased leaves) in comparison to healthy/less infected leaves in Japanese spindle ( Euonymous japonicus ) (Zhang et al ., 2019b), pumpkin ( Cucurbita moschata ) (Zhang et al ., 2018) and English oak ( Quercus robur ) (Jakuschkin et al ., 2016) (reviewed in (Panstruga & Kuhn, 2019)). In the E. japonicus study, the authors noticed a reduction in bacterial and fungal diversity, associated with a general decrease in relative abundance (RA) at the genus level (Zhang et al ., 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the richness and diversity of the fungal community was found to be reduced in pumpkin leaves heavily infected by powdery mildew ( Podospharea sp.) (Zhang et al ., 2018). Marked changes in the composition of foliar fungal and bacterial communities were also observed in Erysiphe alphitoides-colonized oak (Jakuschkin et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that could have contributed to environmental heterogeneity is the presence of rice pathogens. Several recent studies have indicated both that the impact of microbial communities on the course and outcome of host diseases can be substantial, and that host diseases can reciprocally have a large impact on microbial community compositions (Berendsen et al ., 2012; Ritpitakphong et al ., 2016; Koskella et al ., 2017; Zhang et al ., 2018; Vannier et al ., 2019). We have recently shown that the SRBSDV was prevalent in 2016 in the Malizhai HHRTS and that 23 of the 166 rice plants examined in the present study were infected by SRBSDV (Alonso et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%